Horizontal transfer of nuclear DNA in transmissible cancer - Kevin Gori; Adrian Baez-Ortega; Andrea Strakova; Maximilian R. Stammnitz; Jinhong Wang; Jonathan Chan; Katherine Hughes; Sophia Belkhir; Maurine Hammel; Daniela Moralli; James Bancroft; Edward Drydale; et al. (Proceedings of the National Academy of Sciences, 2025)
Horizontal transfer of nuclear DNA between cells of host and cancer is a potential source of adaptive variation in cancer cells. An understanding of the frequency and significance of this process in naturally occurring tumors is, however, lacking. We screened for this phenomenon in the transmissible cancers of dogs and Tasmanian devils and found an instance in the canine transmissible venereal tumor (CTVT). This involved introduction of a 15-megabase dicentric genetic element, composed of 11 fragments of six chromosomes, to a CTVT sublineage occurring in Asia around 2,000 y ago. The element forms the short arm of a small submetacentric chromosome and derives from a dog with ancestry associated with the ancient Middle East. The introduced DNA fragment is transcriptionally active and has adopted the expression profile of CTVT. Its features suggest that it may derive from an engulfed apoptotic body. Our findings indicate that nuclear horizontal gene transfer, although likely a rare event in tumor evolution, provides a viable mechanism for the acquisition of genetic material in naturally occurring cancer genomes.